Mathematical modelling of fineness ratio effects on aerodynamic characteristics of an airship design using computational analysis - Jalasabri, Jafirdaus (2018)
Airships used to be the primary passengers' air transportation means before the jet aircraft took over their role. This happened due to the operational safety concerns after several fatal accidents involving the airships. In recent times however, modern airship designs have been improved and their operational efficiency is said to be better than jet aircraft in many areas. This leads to the idea that airships can be used to revolutionize the current mass public transportation means that are facing several issues of low operational effectiveness and worsened traffic congestion. Though recent airship designs have many advantages, they are not developed for use as a mass public transportation vehicle. To accommodate more passengers onboard, these airship designs might be required to be sized or scaled up and this subsequently affects their aerodynamic performance due to their modified external shape. Therefore, in developing successful airship designs for public transport purposes, it is important for designers to fully understand the effect of the design on the performance of the airship. The external shape design changes can be aptly captured by design fineness ratio parameter of the airship, which is defined as the ratio of the airship's length to its maximum width. Nonetheless, there is a general lack of aerodynamic models that are established for airship design purposes and this is the main identified gap to be addressed in this study. Specifically, the aim of this research work is to establish the effects of design fineness ratio of an airship towards its aerodynamic performance. The Atlant-100 airship is chosen as the reference design model for this study. An approximate computer-aided design (CAD) model of the Atlant-100 airship is constructed using CATIA software and it is applied in computational fluid dynamics (CFD) simulation analysis using StarCCM+ software. In total, 36 simulation runs are executed with different combinations of values for fineness ratio, altitude and velocity. The obtained CFD simulation results are then statistically analyzed using Minitab software to evaluate the significance of the design fineness ratio effects and formulate the mathematical model between the design fineness ratio and the aerodynamic lift and drag forces of the airship design. From the obtained simulation results, it has been found that smaller fineness ratio for Atlant-100 model will correspond to higher aerodynamic lift and drag forces. As in the case simulated in this study, the smallest fineness ratio of 0.93 has been shown to correspond to the highest value of generated lift coefficient while having similar comparable value of generated drag coefficient with the other fineness ratios. This highlights that a smaller fineness ratio of the airship design is more suitable for the mass public use. In addition, from the statistical analysis done, the effects of the fineness ratio to the generated aerodynamic lift and drag forces can be said to be significant. The constructed mathematical models to capture these effects have also been validated with a few goodness-of-fit tests. For the regression model of fineness ratio impact on the lift coefficient, it has R2 value of 0.941. When its predictive accuracy is tested with some simulated random cases, the maximum error obtained is only 6%. On the other hand, for the regression model of the fineness ratio impact on drag coefficient, the R2 value is 0.962 and the maximum predictive error from the simulation random cases test is only 9%. All in all, it can be concluded that the constructed regression models have a good predictive capability to predict the impact of the design fineness ratio on the aerodynamic performance of the airship. With the results from this study, designers can make use of the regression models to predict the right fineness ratio of the airship design for a given mission profile based on expected aerodynamic performance, or vice versa.